2018
DOI: 10.1017/s1431927618015465
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Photothermal Pathways via in Situ Laser Heating in the Transmission Electron Microscope: Recrystallization, Grain Growth, Phase Separation, and Dewetting in Ag0.5Ni0.5 Thin Films

Abstract: A new optical delivery system has been developed for the (scanning) transmission electron microscope. Here we describe the in situ and “rapid ex situ” photothermal heating modality of the system, which delivers >200 mW of optical power from a fiber-coupled laser diode to a 3.7 μm radius spot on the sample. Selected thermal pathways can be accessed via judicious choices of the laser power, pulse width, number of pulses, and radial position. The long optical working distance mitigates any charging artifacts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…S13). The above results show that such a process provided a green chemical separation for flavonoids with fewer steps and lower energy consumption than the traditional organic solvent extraction method, preparation liquid chromatography and capillary electrophoresis (Pyo et al, 2009;Liu et al, 2014;Wu et al, 2018b).…”
Section: Discussionmentioning
confidence: 76%
“…S13). The above results show that such a process provided a green chemical separation for flavonoids with fewer steps and lower energy consumption than the traditional organic solvent extraction method, preparation liquid chromatography and capillary electrophoresis (Pyo et al, 2009;Liu et al, 2014;Wu et al, 2018b).…”
Section: Discussionmentioning
confidence: 76%
“…The sample is irradiated with a fiber-coupled 1.58 eV laser diode with tunable optical power up to 215 mW focused to ~ 5 µm diameter. The sample is tilted at 30° and the unpolarized Gaussian laser spot is aligned and focused to the coincident (S)TEM electron point (see 58 for system details). The laser is operated in cw mode at 1.01 × 10 9 W/m 2 for all laser-on results presented here.…”
Section: Eel and Eeg Measurementsmentioning
confidence: 99%
“…Pulsed and continuous wave (cw) photothermal heating and excitation can both be achieved. In particular, we have studied the recrystallization, grain growth, phase separation, and dewetting of an Ag 0.5 Ni 0.5 film 58 , and resonant cw sEEG and sEEL in nanostructures resulting from a dewet silver film 59 .…”
mentioning
confidence: 99%
“…Using a 215 mW 785 nm single-mode fiber coupled laser diode producing an ~8 µm diameter Gaussian spot, Liu et al reported sEELS and EEGS responses of individual plasmonic nanoparticles [3]. By linearly varying the laser irradiance in the range of 0.5-4×10 8 W/m 2 , Liu et al were able to observe equivalent sEELS and EEGS probabilities without excessive heating.…”
Section: Statesmentioning
confidence: 99%